2015
DOI: 10.1111/jgs.13597
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Related‐Problem Outcomes and Program Satisfaction from a Comprehensive Brown Bag Medication Review

Abstract: Older adults found the medication review helpful and implemented 63% of the DRP recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…They reported the same DRP prevalence of 93% for 182 patients (a mean of 2.5 DRPs per patient, SD 1.5) as in our study (Milos et al , 2013 ). Our results for the polypharmacy subgroup (67% of the DelpHi-MV study participants with five or more prescription medications) are comparable to the 95% prevalence of at least one DRP observed in a recent analysis of participants from senior centers and residential facilities in the USA aged 60 years and older (mean age 75.9 ± 8.5) taking five or more medications (O'Connell et al , 2015 ). A high number of drugs taken increase the number of DRPs in persons both with dementia and without dementia, as has been shown in previous studies (Lau et al , 2010 ; Kaufmann et al , 2015 ; Lavan and Gallagher, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…They reported the same DRP prevalence of 93% for 182 patients (a mean of 2.5 DRPs per patient, SD 1.5) as in our study (Milos et al , 2013 ). Our results for the polypharmacy subgroup (67% of the DelpHi-MV study participants with five or more prescription medications) are comparable to the 95% prevalence of at least one DRP observed in a recent analysis of participants from senior centers and residential facilities in the USA aged 60 years and older (mean age 75.9 ± 8.5) taking five or more medications (O'Connell et al , 2015 ). A high number of drugs taken increase the number of DRPs in persons both with dementia and without dementia, as has been shown in previous studies (Lau et al , 2010 ; Kaufmann et al , 2015 ; Lavan and Gallagher, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…Due to the use of different MRP classification systems, it is challenging to make sound comparisons with other studies. However, in relation to type, i.e., unnecessary use of medication (and number of MRPs), our findings from this rural area are consistent with former studies from Norway, Sweden, Switzerland, and the USA [10,[29][30][31][32]. In a recent study using the same classification tool as we did, Devik et al found a mean of 3.7 MRPs per nursing home resident.…”
Section: Medication Use and Medication Related Problemssupporting
confidence: 92%
“…Previous studies have assessed patient satisfaction after providing pharmacy services delivered by pharmacists in the community . Assessment of services has been published from many countries including England, Michigan (United States), Spain and Australia …”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Previous studies have assessed patient satisfaction after providing pharmacy services delivered by pharmacists in the community. [7,15] Assessment of services has been published from many countries including England, [1,16] Michigan (United States), [17] Spain [18] and Australia. [19] We have previously reported the results of a study aimed at assessing the impact of an MMR service on the type and frequency of TRPs, and certain clinical outcomes in outpatients with chronic conditions who visited community pharmacies.…”
Section: Introductionmentioning
confidence: 99%